2002
DOI: 10.1038/sj.cgt.7700490
|View full text |Cite
|
Sign up to set email alerts
|

Hematoprotection and enrichment of transduced cells in vivo after gene transfer of MGMTP140K into hematopoietic stem cells

Abstract: The overexpression of mutant forms of O 6 -methylguanine -DNA -methyltransferase ( MGMT ), resistant to the MGMT inhibitor O 6 -benzylguanine ( BG ), protects hematopoietic cells from the toxicity of combined BG plus O 6 -alkylating agent chemotherapy. To evaluate the feasibility of this approach for clinically relevant O 6 -alkylating agents, combined therapy with BG and two chloroethylnitrosourea -type drugs, ACNU or BCNU, or the triazene derivative temozolomide ( TMZ ) was investigated in a murine bone marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 38 publications
1
44
0
Order By: Relevance
“…Strategies for selective enrichment of donor hematopoietic stem cells to enhance engraftment were initially developed as a treatment for myelosuppression. There are many studies which have investigated various drug resistance-mediated in vivo selection enrichment strategies [7][8][9][10][11][12][13] among which, the most effective strategy uses O 6 -methylguanine-DNA-methyltransferase (MGMT) (P140K) gene-mediated drug resistance [14][15][16][17][18][19]. MGMT (P140K) is a mutant form of the drug resistance gene MGMT.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies for selective enrichment of donor hematopoietic stem cells to enhance engraftment were initially developed as a treatment for myelosuppression. There are many studies which have investigated various drug resistance-mediated in vivo selection enrichment strategies [7][8][9][10][11][12][13] among which, the most effective strategy uses O 6 -methylguanine-DNA-methyltransferase (MGMT) (P140K) gene-mediated drug resistance [14][15][16][17][18][19]. MGMT (P140K) is a mutant form of the drug resistance gene MGMT.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been successful in protecting against the hematopoietic toxicity of methotrexate with dihydrofolate reductase 2,3 ; against placitaxel, doxorubicin, and vinblastine toxicity using the multidrug resistance gene-1 (MDR1) 4,5 ; and toxicity associated with 1,3-bis-(2-chloroethyl)-1-nitrosourea (BCNU) and 1-(2-chloroethyl)-3-cyclohexyl-1-nitrosourea (CCNU) with O6-methylguanine DNA methyltransferase (MGMT). [6][7][8][9] Retroviral transduction of mobilized peripheral blood progenitor cells has been used in human clinical trials to transfer heterologous genes into hematopoietic cells. 10,11 Several clinical gene transfer trials have demonstrated the feasibility of this approach with retroviral vectors carrying MDR1 in patients being treated with chemotherapeutic agents for cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of MGMT provides resistance to monofunctional methylating agents such as dacarbazine and procarbazine as well as bifunctional chloroethylating agents such as the nitrosoureas like 1,3-bis(2-chloroethyl)-1-nitrosourea (BCNU) or carmustine, ACNU or nimustine and temozolomide. 65,66 AGT expression shows considerable variation in mammalian tissues. For instance, liver cells contain high AGT activity while HSCs possess low activity, explaining the prolonged myelosuppression after nitrosourea treatment.…”
Section: Methyl-guanine Methyl Transferasementioning
confidence: 99%